A multidisciplinary approach to heart failure care in the hospital: improving the patient journey. Issue 3 (27th May 2022) - Rao, Vijay U.; Bhasin, Atul; Vargas, Jesus; Arun Kumar, Vijaya
ABSTRACT: Background: Despite advancements in care for patients with heart failure (HF), morbidity and mortality remain high. Hospitalizations and readmissions for HF have been the focus of significant attention among health care providers and payers, with an eye toward reducing health care costs. However, considerable variability exists with regard to inpatient workflows and management for patients with HF, which represents a significant opportunity to improve care. Objective: Here we provide a summary of optimal inpatient management strategies for HF, focusing on the multidisciplinary team of emergency medicine providers, admitting hospitalists, cardiovascular consultants, pharmacists, nurses, and social workers. Methods: The patient journey serves as the template for this review article, from the initial presentation in the emergency department, to decongestion and stabilization, optimization of guideline-directed medical therapy, and discharge and appropriate disposition. Conclusion: This review aims not to be proscriptive but rather to provide best practices that are clinically relevant and actionable, with the goal of improving care for patients during the sentinel hospitalization for HF.